2020
DOI: 10.1007/s12350-018-1309-5
|View full text |Cite
|
Sign up to set email alerts
|

18F-fluorodeoxyglucose use after cardiac transplant: A comparative study of suppression of physiological myocardial uptake

Abstract: Suppression of physiological myocardial FDG uptake after cardiac transplantation is feasible. The usefulness of heparin in the suppression is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Entre os diversos esquemas de preparo indicados, o uso do jejum prolongado de 12 horas a 18 horas antes da injeção do radiotraçador é um dos mais aplicados, bem como a utilização de uma dieta rica em lipídios e proteínas, enquanto o uso da heparina não é consensual. 123,124 O marco diagnóstico de atividade inflamatória é a captação focal do 18 F-FDG no miocárdio, enquanto há significado prognóstico a presença de captação de 18 F-FDG no VD e a presença de captação inflamatória em áreas de hipoperfusão, as denominadas áreas de discordância (mismatch): metabolismo aumentado com perfusão reduzida. 124 A utilização do PET com 18 F-FDG também é empregada para acompanhamento da resposta ao tratamento na sarcoidose cardíaca e para avaliação da atividade da doença extracardíaca.…”
Section: Radiotraçadores Para Tomografia Por Emissão De Pósitrons (Sp...unclassified
“…Entre os diversos esquemas de preparo indicados, o uso do jejum prolongado de 12 horas a 18 horas antes da injeção do radiotraçador é um dos mais aplicados, bem como a utilização de uma dieta rica em lipídios e proteínas, enquanto o uso da heparina não é consensual. 123,124 O marco diagnóstico de atividade inflamatória é a captação focal do 18 F-FDG no miocárdio, enquanto há significado prognóstico a presença de captação de 18 F-FDG no VD e a presença de captação inflamatória em áreas de hipoperfusão, as denominadas áreas de discordância (mismatch): metabolismo aumentado com perfusão reduzida. 124 A utilização do PET com 18 F-FDG também é empregada para acompanhamento da resposta ao tratamento na sarcoidose cardíaca e para avaliação da atividade da doença extracardíaca.…”
Section: Radiotraçadores Para Tomografia Por Emissão De Pósitrons (Sp...unclassified
“…Increasing the sensitivity and specificity of 18 FDG-PET for the detection of cardiac inflammatory conditions are reliant on preparation protocols and adequate patient adherence to those protocols. Felix et al 3 have demonstrated in their small trial that the use of 18 FDG-PET is potentially a feasible monitoring modality in cardiac transplant recipients. We look forward to emerging trials to evaluate further assessment of patient preparation protocols in cardiac transplant recipients with varying degrees of rejection.…”
Section: Resultsmentioning
confidence: 99%
“…Felix et al's 3-year prospective study 3 compared the effectiveness of three preparations in suppressing physiological myocardial 18 FDG uptakes in all 10 cardiac Figure 1. Cross section of the heart (nontransplanted) using 18 FDG-PET/CT demonstrating appropriate physiological FDG cardiac suppression following the administration of a high-fat, low-carbohydrate preparation protocol in a noncardiac transplant patient.…”
Section: Pet and The Post-transplant Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have evaluated the feasibility of 18 F-FDG PET imaging for the detection of inflammation related to rejection in humans and have concluded that this modality is potentially feasible for monitoring rejection, though clinical trials and correlation with pathology are necessary. 52 Finally, a research group has shown that PET CT imaging of macrophage-avid nanoparticles can detect rejection of heart allografts in mice and predicts organ survival which may offer a quantitative and non-invasive alternative to endomyocardial biopsies in heart transplant recipients, though enhancement of the nanoparticles pharmacokinetics is required for clinical translation in humans. 53 …”
Section: Discussionmentioning
confidence: 99%